(untitled) (UNWE Yearbook, 2021)
The objective of the research is to outline the main trends in the economic relations between the European Union and the Republic of Korea. The research methods used in the study involve retrospective, comparative and content analysis, as well as table presentation of empirical data for the relations between the two countries. The paper is of conceptual character. The thesis of the research is that the Free trade agreement (FTA) between the two countries is beneficial to both parties but changes in trade flows trends ??are difficult to attribute clearly, as other macroeconomic factors are also in place. The results of the research involve several major findings. The slow GDP growth of the EU and the depreciation of the euro against the South Korean won over the past five years are obvious. Korea’s exporters have a higher rate of utilization of preferences than European companies (there are also large differences between the EU Member States). Two key reasons are at the heart of this observation - first, Korea’s exporters, which are often large export family conglomerates, are experienced and resourceful when it comes to administrative customs procedures, while the EU industry is more fragmented. Second, the "direct transport clause" of the agreement does not allow some EU exporters to use their regional centers in Asia to benefit from FTA preferences. The conclusion of the research is that despite the overall positive assessment of the bilateral economic relations, specific concerns remain on both sides.